¿Una guerra civil entre los incrédulos? Las críticas de Voltaire al Système de la nature de Holbach - Ratto, Adrián (2020)
The aim of this paper is to examine Voltaire’s criticisms of Holbach after the publication of Système de la nature, with the purpose of illustrating that his position is not as simple as it may at first appear. This, in turn, highlights the important transformations of Voltaire’s ontology in his writings of the 60’s and 70’s and, in a more general way, sheds some light on the discussions on atheism and materialism during the siècle des Lumières.